LAYANAN MANAJEMEN PERPUSATAKAN DI MTs PARADIGMA PALEMBANG - Afriantoni & Loveling (Program Studi Manajemen Pendidikan Islam Fak. Ilmu Tarbiyah dan Keguruan, 2016)
The key informant was the head of libraries and librarians in the informant supporters are MTs Paradigm Palembang. The data collected is a secondary data source that data such as reading books, documentation and official records. And sources of primary data in the form of observations and interviews. Analysis technique used is data reduction, data presentation, and data verification. Based on the results of the study concluded that the procurement and processing of library materials collection will greatly affect the management of the library to be better and more attractive to users of libraries in improving the quality of the library. The factors which are supporting government aid and parents and facilities are sufficient. And the inhibiting factor is the absence of an adequate budget. Frequent errors in the purchase of library materials by publishers, such as library materials ordered are often different from what is already in the message.